2013
DOI: 10.1097/jom.0b013e31829b27fa
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Long Working Hours and Depression

Abstract: Long working hours increase current and future risks of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 29 publications
0
25
1
Order By: Relevance
“…Descriptive statistics for the identified eligible ten published studies (54)(55)(56)(57)(58)(59)(60)(61)(62)(63) are presented in supplementary table C, www.sjweh.fi/show_abstract. php?abstract_id=3712.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Descriptive statistics for the identified eligible ten published studies (54)(55)(56)(57)(58)(59)(60)(61)(62)(63) are presented in supplementary table C, www.sjweh.fi/show_abstract. php?abstract_id=3712.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The range of study entry year varied between 1992-2010. Four studies were from Japan (54,58,59,62), two from Canada (56,61), and one each from the UK (57), Sweden (55), France (60), and South Korea (63). In three studies, there were separate estimates for men and women (54)(55)(56).…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And finally, occupational factors were included in addition to model 3 covariates (Model 4). Quantitative workload was left out of multivariable logistic regression analyses because of a strong intercorrrelation with working hours and some recent studies indicated that work demands should be treated as an intermediate variable but not as a confounder [ 17 , 22 ]. The significance level for all statistical analyses was P < 0.05 (two-tailed test).…”
Section: Methodsmentioning
confidence: 99%
“…A work schedule comprises various variables—such as work hours, shift work, and break times between work—that are related to different health conditions, including fatigue and chronic disease. To date, numerous studies have reported the effects of shift work and working hours on workers’ health [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Kecklund and Axelsson reviewed the side effects of shift work with regard to hypertension, type 2 diabetes, stroke, cardiovascular disease, and breast cancer [ 8 ].…”
Section: Introductionmentioning
confidence: 99%